TINJAUAN YURIDIS TERHADAP PERJANJIAN YANG DILARANGDALAM UNDANG-UNDANG NOMOR 5 TAHUN 1999 TENTANG LARANGAN PRAKTEK MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT YANG DILAKUKAN OLEH PELAKU USAHA KERAMBA JARING APUNGDI HARANGGAOLHORISON KABUPATEN SIMALUNGUN - Roida Nababan; Jeremia Saragih (Visi Sosial Humaniora, 2020)
This study aims to analyze the forms of agreement prohibited in Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition carried out by floating net cage business actors in Haranggaol Horison, Simalungun Regency. This study uses a juridical empirical and normative juridical approach, through field research and literature research to obtain primary data and secondary data. Literature study is carried out on statutory regulations and other literature and field research is carried out by interviewing business actors of floating net cages in Haranggaol Horison, Simalungun Regency. The data obtained were then analyzed using a quantitative approach and described by analytical descriptive. The results of the study concluded that the forms of agreements that are prohibited under Law 5 of 1999 carried out by business actors in Haranggaol Horison include oligopoly, price fixing agreements, oligopsony, and vertical integration. To prevent the form of a prohibited agreement, it is necessary to establish a cooperative for floating net cage fish business actors to supervise business competition, direct and mitigate the impact of unfair business competition.